Maintenance Management Practices and Factors Affecting Maintenance of Private University Buildings in Ogun State Nigeria - Osuizugbo, Innocent Chigozie; Olusanya, Babajide Oludayo (Tecno Scientifica Publishing & Society of Tropical Science and Technology, 2023)
Building maintenance management is an efficient and viable technique used for addressing issues with construction's upkeep. Nigerian tertiary institutions have been accused of lacking maintenance culture. Meanwhile, quality and sustainable education is delivered when educational buildings are adequately maintained. The present study seeks to investigate the factors affecting maintenance management of private university buildings in Ogun state Nigeria. Questionnaire survey was utilized as a research instrument to gather information from the maintenance personnel within private universities in Ogun state, Nigeria. The data analysis techniques used were descriptive and inferential statistics. The results revealed that use of poor quality components and materials,no adoption of appropriate maintenance cycle for building maintenance, lack of discernable maintenance culture in the country, and inadequate training and development of maintenance personnel are the top most four factors affecting maintenance management of private university buildings in Ogun state, Nigeria. The study provides insights into the factors affecting maintenance management of university buildings. An understanding of these factors would help tertiary institutions and maintenance personnel facilitate the development of strategies required in minimizing the factors affecting maintenance management practices in tertiary institutions.